2022
DOI: 10.1111/jnp.12284
|View full text |Cite
|
Sign up to set email alerts
|

Sensory sensitivity after acquired brain injury: A systematic review

Abstract: The human brain is constantly bombarded with both external and internal sensory stimulation.Efficient registration and modulation of this sensory stimulation allows us to adapt our behavior to the continuous changes in the environment which is fundamental to human cognition. Acquired brain injury can affect sensory processing resulting in an atypical response to sensory stimulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…This condition is particularly prevalent in individuals with acquired brain injuries, where the conventional processing of sensory information is disrupted [ 63 ]. Such disruptions lead to altered perceptions that significantly influence daily living and functional recovery [ 64 , 65 ]. The heightened sensory input associated with spasticity-related unpleasant sensations may overwhelm the individual’s sensory processing capabilities, leading to a state of sensory overload.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is particularly prevalent in individuals with acquired brain injuries, where the conventional processing of sensory information is disrupted [ 63 ]. Such disruptions lead to altered perceptions that significantly influence daily living and functional recovery [ 64 , 65 ]. The heightened sensory input associated with spasticity-related unpleasant sensations may overwhelm the individual’s sensory processing capabilities, leading to a state of sensory overload.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory Sensitivity Questionnaire . To date, there is no validated sensory sensitivity questionnaire that is adapted to stroke patients and that assesses all sensory modalities (for an overview of the diagnostic tools that are used to assess subjective sensory sensitivity after acquired brain injury, see Thielen et al, 2022). Therefore, in order to systematically assess poststroke subjective sensory sensitivity across different modalities (ie, multisensory, visual, auditory, tactile, olfactory, gustatory, environmental temperature, vestibular sensitivity, and pain), we developed a new, patient-friendly sensory sensitivity questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported a subjective sensory hypersensitivity to sound in 44% of 341 individuals with mild traumatic brain injury (Shepherd et al, 2021) and a subjective sensory hypersensitivity to light in 51% of 86 individuals with mild to severe traumatic brain injury (Goodrich et al, 2014; for more details, see Thielen et al, 2022). Subjective sensory hypersensitivity after brain injury has been associated with longer recovery times and mental health difficulties (Callahan et al, 2018; O’Kane et al, 2014; Shepherd et al, 2021).…”
Section: Subjective Sensory Hypersensitivity and Acquired Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent evidence has pointed toward sensory (hyper)sensitivities being associated with acquired brain injury, leading to the suggestion that these may also be a feature in patients who have had encephalitis [21].…”
Section: Introductionmentioning
confidence: 99%